Percepción de docentes y estudiantes sobre el currículo de estudios de una universidad privada de Lima - Vergara León, Mirtha Jéssica (2012)
This research has the purpose of knowing the perception of students and professors about the curriculum of study that applies in the Master's Degree in Education from a private university in Lima. The type of research is descriptive and the not experimental design of descriptive type. The sample was of 403 students and 20 professors. We used a questionnaire on the curriculum plan elaborated by Calderon (2002) in the three dimensions. The results in relation to the courses, the average of the results of the test applied to the students think agree that they are structured and integrated sufficiently to achieve a formation in teaching and research of high quality as like as the programming of academic activities and the courses of investigative training. Also the average of the results of the test applied to the professors they agree totally with the structured courses, the programming of the academic activities and the courses of investigative training.